Cutaneous Larvae Migrans Treated with a Single Dose of Ivermectin. (16th November 2022) - Harrison, Iris S.; Lukose, Kiran; Dass, Bhagwan; Radhakrishnan, Nila S.
Abstract : Hookworm-related cutaneous larva migrans (HrCLM) is a clinical diagnosis based on a history of exposure to contaminated soil and is associated with a characteristic red serpiginous lesion that migrates within the epidermis . Our patient presented with a red, tortuous migratory rash with localized pruritus on the left plantar foot of 1-month duration. He lacked recent travel history outside the southeastern United States. Upon admission, he presented with peripheral blood eosinophilia, an uncommon feature of HrCLM. A single dose of ivermectin was sufficient for treatment, and symptoms resolved within 3 days. This case highlights the increased incidence of domestically acquired hookworm infections, explores this epidemiological shift, and emphasizes relevant differential diagnoses.